An update on the status of molecular testing for the indeterminate thyroid nodule and risk stratification of differentiated thyroid cancer. Issue 1 (January 2018) - Nicholson, Kristina J.; Yip, Linwah
Abstract : Purpose of review: Correct identification of malignancy in cytologically indeterminate thyroid nodules is a diagnostic challenge, leading to potentially unnecessary surgery in patients for whom final histology is benign. Similarly, many patients with differentiated thyroid cancer (DTC) undergo aggressive surgical management of tumors, which may ultimately have low-risk histologic features. Use of molecular testing strategies can aid in both the diagnosis of indeterminate thyroid nodules and preoperative risk stratification of DTC. Recent findings: Validation studies of both the Afirma Gene Expression Classifier and Thyroseq Next-Generation Sequencing panel are ongoing. Both tests can be used to help rule out malignancy in indeterminate thyroid nodules. Recent additions to available molecular testing for indeterminate thyroid nodules include the Rosetta microRNA classifier and the augmentation of the ThyGenX gene panel with a microRNA reflex test (ThyraMIR). Mutational analysis of DTC shows that mutation in TERT alone, and in combination with other mutations, portends advanced disease. Summary: Currently available molecular testing modalities are useful for ruling out malignancy in indeterminate thyroid nodules; however, longer-term follow-up studies are needed to confirm that test-negative nodules are truly benign. Analysis of specific gene mutations helps identify aggressive disease to guide prognostication and management, but further study is needed.